2021
DOI: 10.1155/2021/5201682
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Determinants of Antenatal Care Utilization in Kandahar City, Afghanistan

Abstract: Background. Women’s and children’s health is a crucial public health concern that epitomizes the universal platform for Sustainable Development Goals (SDGs). Appropriate and timely care during pregnancy can improve maternal and child health. Objectives. The present study aimed at determining the magnitude and determinants of antenatal care services’ utilization in Kandahar city. Methods. A community-based cross-sectional study involving 850 women with at least one delivery in the last 2 years was carried out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
(60 reference statements)
4
17
2
Order By: Relevance
“…The frequency of antenatal care visit was high in urban dwellers than rural residents. The finding is in line with previous researches [ 55 , 56 , 64 , 80 ]. Urban residence reduces distance to get services [ 81 – 84 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The frequency of antenatal care visit was high in urban dwellers than rural residents. The finding is in line with previous researches [ 55 , 56 , 64 , 80 ]. Urban residence reduces distance to get services [ 81 – 84 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study 74.38% of women attend antenatal care at least once during their current pregnancy. The finding is consistent with researches in Afghanistan (69.3%) [ 64 ], Southern Ethiopia (76.2%) [ 40 ], Zambia (69%) [ 65 ], Nepal (76.0%) [ 66 ]. The finding is higher than the study in Benishangul Gumuz Region, Ethiopia (37.7%) [ 62 ], Nigeria (65.1%) [ 67 ], Eastern Ethiopia (53.6%) [ 59 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies in Afghanistan have examined utilization of maternal healthcare and the associated in uential factors in recent years (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Of these, one study found that sociodemographic and cultural (woman's role in making the decision to seek PNC service) factors were associated with the utilization of PNC visits (12).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the probability of non-institutional deliveries was greater in women with no ANC visit compared to women with at least 4 ANC visits (16). Four studies from Afghanistan examined the effects of sociodemographic and cultural factors on the utilization of ANC services (17,(19)(20)(21). Among the four studies, one reported that women's education, women's intention for pregnancy, and place of residence were in uential on the use of ANC services (at least 4 visits) (17).…”
Section: Introductionmentioning
confidence: 99%